Thich Nhat Hanh’s Naturalism and Nondualism in a Trans-Different Perspective - Ephraim Meir (Religions, 2025)
The purpose of this study is to describe Thich Nhat Hanh’s naturalism and nondualism and to situate his views in a “trans-different” perspective. I ask whether his thoughts are compatible with other worldviews that work with the notion of justice. I first describe Nhat Hanh’s attitude towards nature. I then demonstrate how his non-separation from nature paves the way for an interconnectedness with all and how his nonduality leads him to a universal belonging. Finally, juxtaposing Nhat Hanh’s nondualism and a justice-oriented approach, I argue that in a “trans-different” perspective different approaches to suffering and peace may learn from each other and complement each other.